Film marketing - Kerrigan, Finola; ScienceDirect eBooks (Amsterdam ; Boston ; London : Elsevier/Butterworth-Heinemann, 2010)
Film Marketing is the first book to consolidate existing literature into a well informed and academically sound textbook. The book focuses on the film industry as a whole, which incorporates popular (mainstream) fiction films (usually) in English, non English language fiction films, documentary films and art house films. In doing so, it is firmly embedded in the global film industry. Although the film industry is global, it is dominated by the Hollywood major studios, and as such, discussion of the Hollywood film industry will be highlighted. But, unlike other film marketing books on the market, this book also highlights other successful film industries, such as Korea, Nigeria and India, as well as looking at examples of film marketing practices from a range of other countries which provide interesting case studies from Denmark, France, the UK and Hong Kong. Film Marketing offers the student a unique combination of theory and practice and written in accessible student-friendly manner, presents an appealing and must-have text for anyone studying film.
Chapter One: Introduction; Chapter Two: The Origins and Development of the Film Industry; Chapter Three: The development of film marketing practices; Chapter Four: Structural considerations and film marketing; Chapter Five: The film marketing mix; Chapter Six: Consumer selection of films. ; Chapter Seven: Film marketing materials; Chapter Eight: The film marketing calendar; Chapter Nine: Social marketing, equality and diversity: The role of film marketing; Chapter Ten: The impact of technology on film marketing practices; Chapter Eleven: Case studies; Chapter Twelve: Conclusions and recommendations.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Motion pictures -- Marketing; BUSINESS & ECONOMICS -- Industries -- Media & Communications; TECHNOLOGY & ENGINEERING -- Telecommunications; Motion pictures -- Marketing; Electronic books